2017
DOI: 10.1177/0093854817736345
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline as a Result of Incarceration and the Effects of a CBT/MT Intervention: A Cluster-Randomized Controlled Trial

Abstract: This study primarily tests whether incarceration negatively affects cognitive functioning; namely emotion regulation, cognitive control, and emotion recognition. As a secondary interest, we test protective effects of a Cognitive Behavioral Therapy/Mindfulness Training (CBT/MT) intervention. Dormitories containing 197 incarcerated males aged 16–18 were randomly assigned to either a CBT/MT program or an active control condition. A cognitive task was administered pre-treatment and again four months later, upon tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 128 publications
(197 reference statements)
2
22
0
Order By: Relevance
“…For example, two recent studies, respectively in a Dutch and U.S. prison, investigated the potential negative effects of the impoverished prison environment on a detainee's neurocognitive functioning. In line with these studies and earlier hypotheses, both studies showed that brain functions connected with self-regulation declined after 3-4 months of imprisonment (Meijers et al 2018;Umbach, Raine, and Leonard 2018).…”
Section: Human Rights: the Obligation To Facilitate Resocializationsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, two recent studies, respectively in a Dutch and U.S. prison, investigated the potential negative effects of the impoverished prison environment on a detainee's neurocognitive functioning. In line with these studies and earlier hypotheses, both studies showed that brain functions connected with self-regulation declined after 3-4 months of imprisonment (Meijers et al 2018;Umbach, Raine, and Leonard 2018).…”
Section: Human Rights: the Obligation To Facilitate Resocializationsupporting
confidence: 86%
“…Think, for example, of obliged participation in treatment programs for sexual offenders or drug addicts. In addition, imprisonment is often intended (at least in part) to stimulate self-reflection and to deter future offending, and may involve unintended changes of brain and mental states as well (Umbach, Raine, & Leonard 2018;Meijers et al 2018). Although these traditional interventions appear to induce mental changes, it is open for debate whether they should be considered as infringing fundamental rights over the mind (Bublitz 2020b;Douglas 2018).…”
Section: Human Rights: Freedom Of Thought and Mental Integritymentioning
confidence: 99%
“…Data collected from three of the studies were reported in more than one article (e.g., a thesis and a published article). Data were extracted from all these articles as they reported complementary data (An et al, 2019; Himelstein, 2010; Himelstein et al, 2012; Leonard et al, 2013; Umbach et al, 2018; Xu et al, 2016). A detailed illustration of the study selection process is portrayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Treatments designed to address the issues associated with psychophysiological differences are typically behavioral in nature, targeted at associated symptoms. Studies of mindfulness have suggested its utility in improving autonomic functioning (Delgado-Pastor, Perakakis, Subramanya, Telles, & Vila, 2013) and emotion regulation (Umbach, Raine, & Leonard, 2018), which may better help individuals with reactive aggression and hyperarousal. Hypo-arousal has been associated with impaired emotional intelligence (Ling et al, 2018a), but emotional intelligence training programs have shown some promise in reducing aggression and increasing empathy among adolescents and increasing emotional intelligence among adults (Castillo, Salguero, Fernandez-Berrocal, & Balluerka, 2013; Hodzic, Scharfen, Ropoll, Holling, & Zenasni, 2018), and in reducing recidivism (Megreya, 2015; Sharma, Prakash, Sengar, Chaudhury, & Singh, 2015).…”
Section: Discussionmentioning
confidence: 99%